The Implementation of Bī’ah Lughawiyyah in Improving the Basic Arabic Speaking Skills of Students at Ar-Raudlatul Hasanah Islamic Boarding School: A Case Study of the First-Year Students' Dormitory - Yudi Irawan; Harik Aziz Faisal; Muhammad Ridwan Hafiz Hulu (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to describe the implementation of bī’ah lughawiyyah (Arabic language environment) in improving the basic Arabic speaking proficiency of first-year students at Pondok Pesantren Ar-Raudlatul Hasanah. As the primary language of Islamic scholarship, Arabic is essential for students to master, particularly in the area of speaking skills (mahārah al-kalām). This study employed a descriptive qualitative approach, with data collected through observations, interviews, and documentation conducted in the dormitory for newly enrolled students. The findings reveal that the bī’ah lughawiyyah was implemented through various language-based activities, including mufradāt (vocabulary enrichment), muḥādatsah (conversation practice), muḥāḍarah (speech practice), and the use of Arabic in daily communication. The implementation of these activities was found to positively influence students' language habituation and improve their Arabic speaking skills. However, several challenges were identified, including students' inconsistent use of Arabic, limited instructional time, and insufficient commitment among some supervisors and teachers to consistently maintain the Arabic-speaking environment. Supporting factors included the active involvement of teachers, a structured monitoring system, and the application of educational disciplinary measures. Therefore, establishing a conducive Arabic language environment is a key factor in the successful development of Arabic language learning, particularly in fostering communicative competence.